The Effects of Digital Game-Based Learning on Arithmetic and Selective Attention in Students with Dyscalculia - Yusra Zaki Aboud; Mamdouh Mosaad Helali; Rommel Mahmoud AlAli; Mohammed Saeed Al-Qahtani; Anees Abdullatif Mashal (Emerging Science Journal, 2025)
The study aimed to investigate the effect of Digital Game-Based Learning (DGBL) on numeracy skills and selective attention among primary school students with dyscalculia in Saudi Arabia. The researchers used a mixed quasi-experimental approach. Ninety randomly selected female fifth-grade students were divided into two groups. The experimental group (n= 45) used the Lumosity cognitive training platform (Raindrops and Memory Match games). The control group (n=45) received traditional mathematics instruction. The students were assessed before and after the intervention using the arithmetic learning difficulties test and the selective attention test developed by researchers. The results showed statistically significant improvements in the skills of students in the experimental group in arithmetic and selective attention. Quantitative analysis revealed a very large effect size (η² = 0.97) for the DGBL intervention on both scales. The perceptions of 32 teachers, gathered through semi-structured interviews, confirmed these findings, with the majority reporting significant improvements in the math skills and auditory and visual attention of students with dyscalculia. Qualitative data demonstrated the effectiveness of the DGBL program in increasing student engagement and motivation, reducing anxiety, and providing more enjoyable and engaging learning than traditional teaching. These findings advocate for the broader integration of DGBL into special education curricula in Saudi Arabia to create more inclusive, engaging, and effective learning.